2014
DOI: 10.2319/071514-495.1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of text messaging on oral hygiene effectiveness

Abstract: Objective: To investigate whether text message reminders regarding oral hygiene have an effect on plaque removal in orthodontic patients. Materials and Methods: In this randomized, controlled clinical trial, 50 orthodontic patients were assigned to either a text message or control group. Patients in the text message group received 12 text messages over the course of 4 weeks and one text message for 8 weeks thereafter. Photos were taken at baseline (T0), at 4 weeks after baseline (T1), and at 12 weeks after bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 25 publications
0
53
0
2
Order By: Relevance
“…Nineteen articles met all inclusion criteria [35-53]. Most (n=15) included texting interventions [35-41,43-45,47-49,52,53], and only 4 studies had mobile phone–based app interventions [42,46,50,51]. The primary aim of the interventions was to improve adherence to clinic attendance (primary care, gynecology, mental health) [35,36], contraception use [37-39], oral health and hygiene in orthodontic patients [46,47], physical activity and weight management [48-51], sun-protective measures [52], and HPV vaccination [53]; or to reduce risky behavior, including unsafe sex [40-42], smoking [45], and alcohol misuse [43,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen articles met all inclusion criteria [35-53]. Most (n=15) included texting interventions [35-41,43-45,47-49,52,53], and only 4 studies had mobile phone–based app interventions [42,46,50,51]. The primary aim of the interventions was to improve adherence to clinic attendance (primary care, gynecology, mental health) [35,36], contraception use [37-39], oral health and hygiene in orthodontic patients [46,47], physical activity and weight management [48-51], sun-protective measures [52], and HPV vaccination [53]; or to reduce risky behavior, including unsafe sex [40-42], smoking [45], and alcohol misuse [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Nine were conducted in the United States [36-41,47,50,53], 3 in Switzerland [35,44,45], 2 in Hong Kong [48,49], and 1 each in Colombia [42], Wales [43], Italy[46], New Zealand [51], and Germany [52]. Most (n=9) were conducted in a clinic setting [35-39,46,47,53], 3 in a university [41-43], 2 in vocational schools [44,45], 1 in secondary schools [48], 1 in an emergency department [40], 1 in a clinic and summer camp [52], 1 in both a clinic and Web-based environment [50], and 1 at participants’ home [51]. Most (n=12) enrolled younger adolescents (age ≥12 and < 18 years) [35,36,41,45-53], 6 enrolled older adolescents (age ≥18 and <24 years) [37,38,40,42-44], and 1 reported only an age range of 13-21 years [39].…”
Section: Resultsmentioning
confidence: 99%
“…Since numerous studies have shown that sending short message service (SMS) text messages as prompt cues is an effective way for establishing behavior changes and improving oral hygiene during fixed orthodontic treatment [48-50], the app also provided an option for setting reminders for oral health behavior tasks (including monitoring of behavior and dental plaque) and the use of the brushing timer (targeting determinants: “cues to action or habit formation”). The reminders were sent as push notifications.…”
Section: Resultsmentioning
confidence: 99%
“…IM was proven to be a suitable method for developing health promotion programs for various health issues [64-66]. In the field of orthodontics, authors did not describe the process of program development explicitly in their publications [41,42,48-50,67-71]. This limited opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Bowen and colleagues [14] have shown text messaging to be an effective tool for improving oral hygiene compliance in orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%